Applying Actual Usage Inventory Management Best Practice in a Health Care Supply Chain - Varghese, Vijith; Rossetti, Manuel; Pohl, Edward; Apras, Server; Marek, Douglas (International Journal of Supply Chain Management, 2012)
The demand characteristics and optimal control policies for pharmaceutical items within a multi-echelon provider network are examined within the framework of a case study. This paper lays a foundation for the better understanding of the application and acceptance of more advanced inventory control practices driven by actual usage data within the health care supply chain. Demand forecasting algorithms were applied to forecast demand for inventory control procedures.  The costs of inventory control models are compared to the current ordering and inventory control strategies to document potential cost savings using both a single echelon analysis and a multi-echelon analysis. The results indicate that there is great potential for significant cost savings within the provider network. It is likely that if other providers adopt such practices that they will be able to better control material supply costs.